A report on practice in industry training in fish preservation. - Mallen, Charito V. (Miagao, Iloilo College of Fisheries, University of the Philippines, 1977)
Preservation of fish by canning is one of the most important method developed during modern times. Canning is done based on the principle of preservation by heat in her mitically sealed containers which has, for each day objective, the prevention of spoilage through micro-biological action. First consideration is the condition of raw material especially if it is perishable, like fish. Today, numerous species of fish are being canned giving emphasis and importance to tuna canning. Tuna is widely used because of relatively high nutritive value and abundance. This report aims to illustrate and explain the steps involved in the processing of tuna. It will likewise evaluate the quality of the finished product and assess the physical features of the canning plant by the way of observations and interview of workers and personnel of the plant.
Keywords: Fish-Preservation.